(untitled) (Journal of Environmental Science and Natural Resources, 2015)
Wheat is the most important cereal crop and staple food of about two billion people around the world and contributes more calories and proteins to the world diet than any other cereal crop. Wheat grain quality is a function of grain composition, principally in proteins, which depends on the genotype and the environment. Protein content is a key quality factor that determines the suitability of wheat for a particular type of product as it affects other factors including mixing tolerance, loaf volume and water absorption capacity. The experiment was conducted at the Bangladesh Agricultural University farm during 2007 to 2010 to study the effects of boron fertilization and sowing dates on the Black point disease of wheat genotypes. The soil was silty loam in texture having pH 6.7, cation exchange capacity 12.6 me/100g soil, organic matter 1.9%, total N 0.09%, available P 7.3 ppm, exchangeable K 0.09 cmol kg-1, available S 12.4 ppm, available Zn 0.8 ppm and available B 0.19 ppm. The wheat varieties used in the experiment were Prodip, Shatabdi and Sourav. Boron was applied @ 0 and 1 kg ha-1 and sowing dates were 18 November, 28 November, 08 December and 18 December. The experiment was laid out in a split-split plot design with a distribution of sowing dates to the main plots, varieties to the sub-plots and boron treatment to the sub-sub plots. All the factors were replicated three times. The total amount TSP, MoP, gypsum and zinc oxide were applied during final land preparation. Nitrogen was applied @ 120 kg ha-1 from urea (46 % N), P @ 20 kg ha-1 from TSP (20 % P), K @ 60 kg ha-1 from MoP (50 % K), S @ 10 kg ha-1 from gypsum (18 % S) and Zn @ 1.5 kg ha-1 from ZnO (78 % Zn). Urea was applied in three equal splits - final land preparation and 30 and 45 days after sowing. Boric acid (17%B) was applied to the B treatment plots prior to sowing. The crop was irrigated 2 times- 21 days (crown root initiation) and 47 days (heading stage) of sowing. Soil samples were analyzed for texture, pH, OM, total N and available P, K, S, Zn, S and B contents. The data were analyzed statistically (Gomez and Gomez, 1984). Boron application exerted a significant increasing effect on the protein content of wheat grain. A. significant variation in the N and protein content of wheat grains was observed among the wheat varieties in both the years. The 28 November sowing recorded the maximum protein content in wheat grains while the minimum value was noted with the 18 December sowing in both the years. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22038 J. Environ. Sci. & Natural Resources, 6(1): 41-45 2013